Pengaruh Pendekatan Pembelajaran Open Ended Terhadap Kemampuan Komunikasi Matematis Siswa MTs di Sumbawa, Indonesia - Amula Putra, Rande Ade; Mauliddin, Mauliddin (Mathematic Education Departement, State Islamic University of Mataram, 2022)
This study aims to determine the effect of the open-ended learning approach on students' mathematical communication skills. This research is a quasi-experimental research (quasi-experimental) with a quantitative approach. This research took place at MTsN 2 West Sumbawa. The population in this study were students of class VII MTS. The research sample was 32 students, of which 16 students were used as participants in the experimental class and 16 students as participants in the control class. The instrument used in this research is a questionnaire. The results showed that there was an effect of the open-ended learning approach on students' mathematical communication skills. With a significant level of a = 0.05; obtained ttable = 2.042 and tcount = 3,672. It is concluded that tcount > ttable then Ho is rejected. Thus, it can be concluded that there is an effect of the open-ended learning approach on mathematical communication skills between students who are taught using an open-ended approach compared to the conventional approach.